Structural and quantitative evidence of α2–6-sialylated N-glycans as markers of the differentiation potential of human mesenchymal stem cells - Hasehira, Kayo; Hirabayashi, Jun; Tateno, Hiroaki (Glycoconjugate journal, 2017)
Human somatic stem cells such as mesenchymal stem cells (hMSCs) have the capacity to differentiate into mesenchymal tissue lineages and to alter immune regulatory functions. As such, they hold promise for use in stem cell-based therapies. However, no method is currently available to evaluate the actual differentiation capacity of hMSCs prior to cell transplantation. Previously, we performed a comprehensive glycan profiling of adipose-derived hMSCs using high-density lectin microarray and demonstrated that α 2–6-sialylation is a marker of the differentiation potential of these cells. Nevertheless, no information was available about the structural details of these of α 2–6-sialylated glycans. Here we used high performance liquid chromatography (HPLC) analysis combined with mass spectrometry (MS) to perform a structural and quantitative glycome analysis targeting both N - and O -glycans derived from early (with differentiation ability) and late (without differentiation ability) passages of adipose tissue-derived hMSCs. Findings in these cells were compared with those from human induced pluripotent stem cells (hiPSCs), human dermal fibroblasts (hFibs) and cartilage tissue-derived chondrocytes. A higher percentage of α 2–6-sialylated N -glycans was detected in early passage cells (24–28 % of sialylated N -glycans) compared with late passage cells (13–15 %). A major α 2–6-sialylated N -glycan structure detected in adipose-derived hMSCs was that of mono-sialylated biantennary N -glycan. Similar results were obtained for the cartilage tissue-derived chondrocytes, Yub621c (28 % for passage 7 and 5 % for passage 28). In contrast, no significant differences were observed between early and late passage hMSCs with respect to α 2–6-sialylated O -glycan percentages. These results demonstrate that levels of α 2–6-sialylated N -glycans, but not O -glycans, could be used as markers of the differential potential of hMSCs.